Passé et avenir d'une rivière montréalaise - Legault, Louise (Histoire Québec, 2024)
Keywords: Lachine; Lachine (canal); Pollution; Égouts

Frère Marie-Victorin, environnementaliste - Audet, René (Bulletin d'histoire politique, 2015)
Keywords: Botanique; Marie-Victorin, Frère

Le Domaine. Une belle histoire qui se poursuit... Les jardins du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc, 2002)
Keywords: Domaine Saint-Sulpice; Jardins

Montréal et son environnement naturel - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Climat; Géographie physique; Voie maritime

Les défis et enjeux du changement vers le développement durable: l'analyse stratégique des muséums nature de Montréal - Procéda, Aude (Université du Québec à Montréal, 2007)
Keywords: Jardin botanique; Musées

La patrimonialisation de l'environnement au Biodôme de Montréal - Crenn, Gaëlle (Culture & Musées, 2003)
Keywords: Patrimoine

Le biodôme de Montréal ou La nature médiatisée: patrimonialisation de l'environnement dans un dispositif d'immersion simulée - Crenn, Gaëlle (Université du Québec à Montréal, 2000)
Keywords: Patrimoine

La néolithisation dans la région de Montréal depuis le Sylvicole moyen tardif: apport archéopalynologique - Landry, Daniel (Université de Montréal, 2012)
Keywords: Géographie physique

Stewardship as Partnership: A Comparative Study of Positive Human-Environment Relationships in East Cree and Suburban Montreal Communities - Forrest, Margaret Anne (Université McGill, 2006)
Keywords: Banlieue; Parcs; Pointe-Claire

"An Ocean of Noise": H.E. Reilley and the Making of a Legitimate Social Problem, 1911-45 - Rudy, Jarrett; Kenny, Nicolas; Fahrni, Magda (Journal of Canadian Studies / Revue d'études canadiennes, 2017)
Keywords: Physique; Université McGill

Le rôle de la connaissance scientifique et sa relation avec le public dans la gestion concertée de l'environnement: le cas d'un site contaminé de la zone portuaire de Montréal - Champagne, Patrick (Université du Québec à Montréal, 2003)
Keywords: Pollution; Port

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Recherche ou lobbyisme ? L’Institut économique de Montréal et le réchauffement climatique depuis 1999 - Lamy, Guillaume (Politique et Sociétés, 2022)
Keywords: Climat; Libéralisme

''L'autoroute est-ouest, c'est pas le progrès!'': environnement et mobilisation citoyenne en opposition au projet d'autoroute est-ouest à Montréal en 1971 - Poirier, Valérie (Bulletin d'histoire politique, 2015)
Keywords: Autoroutes; Groupes populaires

Ville Mont-Royal: cité-jardin vitruvienne - Corboz, André (De la ville au patrimoine urbain: histoires de forme et de sens, 2010)
Keywords: Mont-Royal (quartier); Quartiers

The High Ground: Mansions, Mythology, and the Mountain - Macleod, Roderick (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Paysages; Quartiers

Les lieux de villégiature - Hubert, Ollivier (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Urban Elites, Energy, and Smoke Policy in Montreal during the Interwar Period - Temby, Owen; MacFadyen, Joshua (Urban History Review / Revue d'histoire urbaine, 2016)
Keywords: Montreal Board of Trade

Urban Environments and the Animal Nuisance: Domestic Livestock Regulation in Nineteenth-Century Canadian Cities - Kheraj, Sean (Urban History Review / Revue d'histoire urbaine, 2015)

Des eaux indésirables: Montréal et ses eaux de surface, 1796-1840 - Fougères, Dany (Revue d'histoire de l'Amérique française, 2006)
Keywords: Égouts

Un projet inconnu de Jacques Gréber: La Cité-jardin de Villeray du Domaine Saint-Sulpice à Montréal - Ploegaerts, Léon (Urban History Review / Revue d'histoire urbaine, 2001)
Keywords: Domaine Saint-Sulpice; Quartiers; Villeray

Taming the Jungle in the City: Uprooting Trees, Bushes, and Disorder from Mount Royal Park - Caron, Matthieu (Urban History Review / Revue d'histoire urbaine, 2018)
Keywords: Délinquance; Mont-Royal (parc); Montreal; Parcs; Police

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune

Du biogaz en héritage. Mobilisations autour d’un « gisement » d’énergie dans une décharge urbaine (Montréal, 1986– 2009) - Marrec, Anaël (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Groupes populaires; Pollution

Connaissez-vous Marcelin Wilson? - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Keywords: Hommes d'affaires; Parcs; Philanthropie

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Les rapports à la ville à travers les espaces de loisirs: Montréal, 1881-1940 - Shaffer, Valérie (Université de Montréal, 2009)
Keywords: Parcs; Places publiques; Réformistes

Fruits des institutions et récoltes populaires. Étude sur la portée sociale du jardinage communautaire à Montréal de 1909 à 1990 - Saint-Hilaire-Gravel, Philippe (Université du Québec à Montréal, 2014)
Keywords: Groupes populaires; Jardins

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

Savoirs, mobilisations et construction du risque environnemental de l'automobile durant les long sixties à Montréal - Poirier, Valérie (Université du Québec à Montréal, 2018)
Keywords: Automobile; Groupes populaires; Pollution

Modernizing Mount Royal Park: Montréal Jungle in the 1950s - Caron, Matthieu (Université de Montréal, 2016)
Keywords: Délinquance; Mont-Royal (parc); Montreal Parks and Playgrounds Association; Parcs; Police

La Société pour Vaincre la Pollution comme mouvement démocratique et critique de la société de consommation (1970-1980) - Poirier, Valérie (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2008)
Keywords: Groupes populaires; Pollution

L'état de préparation des intervenants de l'Île de Montréal en l'an 2000 face à des pluies diluviennes comme celles du 14 juillet 1987 - Boissonneau, Julie (Université de Sherbrooke, 2001)
Keywords: Climat

La réduction de gaz à effet de serre et les transports urbains des personnes à Montréal - Gandulfo, Mónica (Université de Sherbrooke, 2000)
Keywords: Automobile; Climat; Transport en commun